Maintenance Financing Analysis Of Oil Palm Order Revenue At PT Laras Astra Kartika - Rena Agustina; Heriyanto Heriyanto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to analyze factors that affect the income of PT Laras Astra Kartika's oil palm plantation business. First, the cost of oil palm production per hectare and maintenance costs on income is analyzed. Then, the data analysis method is used to determine the technical maintenance of oil palm production. It is explained using the formula for the total cost of oil palm production and a financial feasibility test described descriptively. The primary data collection method is data obtained directly from the data source and secondary data, namely data obtained from related agencies. The results showed a strong relationship between the costs of production, maintenance, and mature plantations which affected oil palm income. Furthermore, from the results of financial feasibility, if the value of the R/C Ratio is more significant than one, then the oil palm plantation business of PT Laras Astra Kartika is feasible to be developed financially.